Four new species of Amanita sect. Roanokenses (Basidiomycota) from Western Australia - Davison, Elaine; Giustiniano, Danielle; Barrett, Matt; Syme, Katrina (2023)
Four species of Amanita Pers. are documented from Western Australia. Amanita brunneola E.M.Davison & Giustiniano is described from the Perth region. It is distinguished by its pale brown pileus, white universal veil, globose basal bulb, amyloid, cylindric spores and presence of clamp connections. Amanita cretaceaverruca E.M.Davison & Giustiniano is described from the Perth region and the southern jarrah forest. It is distinguished by its brown pileus, with a thick white warty universal veil, globose or ovoid basal bulb, amyloid, elongate spores and absence of clamp connections. Amanita mallee E.M.Davison, Giustiniano & M.D.Barrett is described from the Shire of Coolgardie. It is distinguished by its white pileus and universal veil, tapered basal bulb, amyloid, cylindric spores and abundant clamp connections. Amanita validiuscula E.M.Davison, Giustiniano & K.Syme is described from the wheatbelt and Yalgoo area. It is distinguished by its white pileus and universal veil, ivory lamellae, fusiform or tapered basal bulb, amyloid, ellipsoid spores and abundant clamp connections. Molecular analysis shows all these species are members of sect. Roanokenses. Amanita brunneola, A. cretaceaverruca and A. mallee form a clade with other species from Australia and New Zealand, which may indicate Gondwanan origin.